Lexical access in production of idioms by proficient L2 learners - Yeganehjoo, Masoomeh; Yap, Ngee Thai (Penerbit Universiti Kebangsaan Malaysia, 2012)
Earlier studies have worked on the hybrid account of idiom representation in the mental lexicon and the need for the superlemma level in the staged process of idiom production. However, not much attempt has been undertaken to explore how idioms are represented in and accessed from the mental lexicon of second language (L2) during speech production. This paper presents the results of a cross-modal priming experiment conducted to explore whether or how idiom representation in L2 lexicon during language production resembles the one in L1 lexicon. Thirty-two Iranian English instructors were asked to memorize a list of English expressions (common idiomatic and literal phrases) and to produce them when presented with both the grammatical subject of the sentence and the prime words (related or unrelated). The results of this study showed a positive effect of priming for both idiomatic and literal phrases implying that every constituent of an idiom could be accessed individually. With related primes, the production of idiomatic expressions was significantly faster than the production of literal phrases, supporting the unitary representation of idiomatic expressions in L2 lexicon during speech production.